OUTCOMES OF SURGICAL AND NON-SURGICAL MANAGEMENT OF SEVERE PANCREATITIS A CROSS-SECTIONAL STUDY AT PUMHS. : .JPUMHS;2024:14:04,124-131. http://doi.org/10.46536/jpumhs/2024/14.04.569 - Mukhtiar Ahmed Abro1, Shahzad Memon3, Sajjad Hussain Qureshi3, Noor Nabi Siyal4, Awais Bashir Larik5, Mohammad Ramzan6 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Severe acute pancreatitis SAP is a life-threatening condition associated with high morbidity and mortality, particularly in resource-limited settings. Surgical and non surgical management strategies remain pivotal in SAP care, with limited data available in the regional context. OBJECTIVE: This study aimed to compare the outcomes of surgical and non-surgical management of SAP, including mortality, complications, and length of hospital stay, at Peoples University of Medical and Health Sciences PUMHS, Nawabshah. METHODS: A cross-sectional study was conducted, including 400 patients diagnosed with SAP based on the revised Atlanta classification. Demographics, management type, complications, mortality, and hospital stay data were analyzed. Statistical tests, including chi square and logistic regression, were applied to determine associations and predictors of outcomes. RESULTS: Of the 400 patients, 61.5% received non-surgical management, while 38.5% underwent surgical intervention. Mortality was significantly higher in the non-surgical group 25% compared to the surgical group 12.5% p < 0.05, particularly among males. Complications such as organ failure and infections were more common in non-surgical patients 28.8% in males vs. 15.5% in females. Surgical management demonstrated improved outcomes, with reduced mortality and comparable hospital stays. Disease severity scores were critical predictors of mortality and prolonged recovery, while gender differences influenced complication rates. CONCLUSION: Surgical management significantly improves outcomes in SAP patients with severe complications. Early disease stratification, timely interventions, and infrastructure development for minimally invasive techniques are essential for optimizing SAP care in resource-limited settings.